KEMAMPUAN PENALARAN STATISTIKA: PENERAPAN MODEL PEMBELAJARAN LC7E DAN PENILAIAN AUTENTIK - Nopita (Jurnal Evaluasi Pendidikan, 2017)
This study aims to determine the effect of LC7e learning model and authentic assessment of students' statistical reasoning abilities. The sample in this research is the fourth semester student of PAI FTIK IAIN Pontianak. The dependent variable is statistical reasoning ability, and the independent variables consist of the differentiated learning model being LC7e and conventional, and the authentic judgements are differentiated into portfolios and written tests. The instrument used is a test of students' statistical reasoning abilities. The method used is quasi-experimental method while the design used is treatment by 2x2 design. The data obtained were analyzed by using two-way analysis of variance (ANAVA).The results of this study indicate that the students' statistical reasoning abilities using the LC7e model will be more effective if given a portfolio assessment. And students' statistical reasoning abilities using conventional models would be more effective if given a written test assessment